INITIAL PUBLIC OFFERING: NEW EVIDENCE FROM INDONESIA - Mindosa, Bonnie; Pasaribu, Pananda (APPS Publications, 2020)
The authority of capital market in Indonesia has been trying to increase the participation of investors and the number of listed firms to boost the economic growth. Recently, the number of listed firms have increased significantly. However, there are firms that are unable to show good financial performance, in fact several firms entered financial distress and delisting from the market. This essay uses newly listed firms between 2012 and 2019. This essay shows that there exists underpricing in the short term (1-3 days) and underperformance in the long term (1-3 years) after going public. This essay recommends that investors should take advantage the underpricing, but they must be smart in selecting newly listed stocks as some may suffer from credit risk and poor corporate governance.